Analysis of Electric Field Distribution for Polluted High Voltage Glass Insulator Using Finite Element Method - Abdullah Z.; Abidin I.Z.; Osman M.; Rahman N.A. (American Institute of Physics Inc., 2024)
This paper describes a finite element method based on electric field distribution for evaluating the electrical performance of an 11 kV high voltage transmission line glass insulator. Glass insulators on wet polluted surfaces were considered. For simulation purposes, the proposed two-dimensional model was designed using AutoCAD software in 2D. Numerical analysis was used to determine the electric field distribution along the glass insulator surface using COMSOL Multiphysics software. It has been shown that a wet polluted surface of a glass insulator has a significant influence on the value of the electric field in the area near the high-voltage end termination. 2023 American Institute of Physics Inc.. All rights reserved.